Analysis of Arabic Learning Books for Grade Twelve at Islamic High School Based on The Curriculum 2013 - Bela Noviana Dewi (Al-Muyassar: Journal of Arabic Education, 2023)
AbstractThis study aims to examine and analyze the suitability of the material contained in the Arabic language book of Madrasah Aliyah Class XII with Core Competencies of the 2013 Curriculum. The method used by the researcher is a qualitative research method. The results of this study indicate that the material in the book follows the Core Competence standards of the 2013 Curriculum, which in each chapter covers aspects of the realm of spiritual attitudes, the realm of social attitudes, the realm of knowledge, and the realm of skills Keywords: Analysis, Teaching Materials, K13 Competency Standards